Maxillary Growth and Speech Outcome in Patient with Cleft Lip and Palate after Two-Stage Palate Repair: A Systematic Review - Mulyadi, Mulyadi; Kreshanti, Prasetyanugraheni; Handayani, Siti; Bangun, Kristaninta (Jurnal Plastik Rekonstruksi, 2012)
Background: The management of patients with cleft lip and palate is complex, where the treatment outcome is judged on the balance between aesthetics, speech, and maxillary growth. Up to now, there is no generally accepted treatment protocol. Every center must find the best-suited protocol treatment for their population. Methods: A systematic review through literature search was conducted for English-language studies in PubMed. This search was conducted in September 2011 using EndNote X3 with keywords: Two-stage Palate Repair and Maxillary Growth and Two-stage Palate Repair and Speech Outcome. Both retrospective and prospective studies on maxillary growth and speech outcome in patient with cleft lip and palate after two-stage palate repair published from 2001 to 2012 were included. Result: From the reviewed of 37 articles, only 14 articles fit the inclusions criteria, three articles discussed the outcome of maxillary growth and speech outcome, eight articles only discussed the maxillary growth and the rest of articles only discussed the speech outcome. Conclusion:From this review we found that most of the two-stage palate repair results in better maxillary growth, but only few of them results in good speech outcome. We will perform further study based on this review to discover a new protocol for the management of palate repair in our center.